2008
DOI: 10.1007/s11605-007-0244-6
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Laparoscopic Versus Open Left Lateral Hepatic Sectionectomy

Abstract: Laparoscopic resection results in reduced operative blood loss and earlier recovery with oncologic clearance and operative time comparable with open surgery. Laparoscopic liver surgery may be considered the approach of choice for tumors located in the left hepatic lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 15 publications
7
91
0
1
Order By: Relevance
“…The first two issues were addressed early in the first part of this decade [2,15,16,17] and oncological efficiency has been recently demonstrated [1,21,22,23,24,25]. However, surgical indications continue to raise concerns especially for the treatment of benign liver lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two issues were addressed early in the first part of this decade [2,15,16,17] and oncological efficiency has been recently demonstrated [1,21,22,23,24,25]. However, surgical indications continue to raise concerns especially for the treatment of benign liver lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This appeared appropriate especially when considering initial concerns regarding tumour dissemination, incomplete tumour resections and involved margins [2,17,18,19,20]. Several centres have now demonstrated the oncological efficiency of the laparoscopic approach [1,21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…In our series no laparoscopic patient had a R1 resection, and the width of free margin did not differ between the two groups (laparoscopy vs. open: 11 mm vs. 7 mm). Intraoperative ultrasonography was used in all patients, and helped to show the tumor extent, its relationship with vessels, and the eventual presence of satellitosis, achieving a clear margin in absence of tactile sensation [15,16]. Another concern about laparoscopic resection of malignancies is the risk of port site tumor recurrence, which was not recorded in our patients.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Previous studies reported that the laparoscopic approach was associated with a shorter length of hospital stay irrespective of the indication, a lower transfusion rate and earlier recovery in patients with benign condition or primary malignancy, even in cirrhotic patients. [5][6][7] This study has the inherited limitations of the retrospective study with small number of patients. The selection criteria for laparoscopic and open surgery were not presented clearly.…”
Section: Editorialmentioning
confidence: 99%